Organizational Communication Strategy at BAZNAS Institution in Raising Zakat Funds in Bandar Lampung City - Mustofa, Muhamad Bisri; Handayani, Layla; Wuryan, Siti (Journal International Dakwah and Communication, 2023)
Social welfare problems are a problem of the entire Indonesian nation that requires the attention of all parties, including the government, the business world and the community. The government tries to overcome social problems through various programs and activities, but the problem is never resolved. In this regard, zakat can act as a source of socio-economic resources for Muslims. This means that the utilization of zakat managed by the Amil Zakat Agency is not only limited to certain activities based on conventional directives, but can also be used for the economic activities of the ummah such as poverty and unemployment assistance programs, using zakat as working capital for activities produced by those in needThe research method in this title is descriptive analysis or qualitative, which is carried out in the field to explain the strategies used in the management of zakat to raise more funds. This research was conducted by applying the study to the National Amil Zakat Agency (BAZNAS) of Bandar Lampung City by using primary data. The results showed that the communication strategy carried out by BAZNAS Institution in collecting people's funds is by implementing interpersonal communication, namely through friendship both formally and informally or by socializing to the public about the National Amil Zakat Agency (BAZNAS). The succession of communication strategies is carried out by intensifying online and offline marketing activities utilizing zakat utilization content and post-utilization reports on zakat funds Communication Strategy The communication strategy applied by the National Amil Zakat Agency in Efforts to Collect zakat is to use interpersonal communication to foster trust, BAZNAS's existence is known to a wide audience through amil silaturrahmi activities, successive information and office location